The effects of cooperative learning on the performance of Grade 11 Mathematics learners in the Oshana educational region, Namibia (Journal for Studies in Humanities and Social Sciences, 2015)
This study sought to determine the effects of cooperative learning on the performance of the Grade 11 learners doing Mathematics on higher level in the Oshana Education Region. The study used a quasi-experimental design. Two Grade 11 classes (each comprising 31 learners) doing Mathematics on a higher level from one school in the Oshana region were purposefully selected; one as a control group and the other as an experimental group. The instruments used to measure the performance in Mathematics were a pre-test and post test. Prior to collection of the data, a pilot study was carried out in a different school to gather information on the appropriateness of the instruments and other administrative logistics. During the main study, the experimental and control groups were separately taught Differentiation a topic from the higher level Mathematics syllabus. The t-test was used to find out whether significant differences existed in the performance of the control and experimental groups. The results showed that significant differences in performance and in the motivation level of the experimental and control group existed at the 0.01 significant level. The findings suggested that cooperative learning improved learners’ performance in Mathematics. The study recommended that Mathematics teachers should place emphasis on learners’ understanding of particular concepts, guiding learners in active learning, providing opportunities for discussion and elaboration and encouraging them to work with peers to enhance learners’ academic performance.